YouTube Marketing - Eagle, Will, author (Hoboken, NJ : John Wiley & Sons Inc., 2019)
YouTube is the top destination for online video. With over a billion viewers around the globe, it's also valuable real estate for marketers looking to get their message out. YouTube Marketing For Dummies shares insight from a former YouTube employee who helped large and small businesses create effective marketing campaigns.